Antara Hukum dan Geopolitik: Peran Amerika Serikat dan Independensi Mahkamah Internasional pada Sengketa Essequibo - Diva Islami Putri Ansor (Dialogia Iuridica, 2025)
The Guyana–Venezuela territorial dispute over the Essequibo has re-emerged following the discovery of offshore oil reserves in 2015 and the growing involvement of the United States (US) through diplomatic support and military cooperation. This study examines the legal limits of third-state involvement under the principle of non-intervention and the intervention mechanism before the International Court of Justice (ICJ), while assessing the impact of US support on perceptions of the ICJ’s impartiality and independence. The research adopts a normative juridical approach with a descriptive-analytical method. Data was collected through library research covering primary legal instruments, relevant jurisprudence, academic literature, and official documents. The findings indicate that, although the ICJ’s institutional independence remains intact, US involvement surrounding the proceedings may generate external pressure that could affect perceptions of impartiality during dispute settlement. Accordingly, the parties should comply with the ICJ’s provisional measures, and third states should limit their support to non-coercive forms.